2012
DOI: 10.1007/s10072-011-0894-8
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of eukaryotic translation initiation factors 3B (EIF3B) inhibits proliferation and promotes apoptosis in glioblastoma cells

Abstract: Eukaryotic initiation factors 3 (EIF3) complex is essential for initiation of protein synthesis for both cells and virus. It consists of 13 subunits (EIF3A to M), among which EIF3B serves as a major scaffolding subunit. However, its functions in human glioblastoma have not been explored yet. Here, we showed that EIF3B was expressed in human glioblastoma (Grade I-IV) and human glioblastoma cell lines (U251, U87, A172 and U373). Loss of function analysis was performed on U87 cells using lentivirus-mediated siRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 12 publications
5
55
0
Order By: Relevance
“…The similar findings were also found in other eIF3 subunits [8,11,18,19]. Clonality and migration are the basis for cancer cells' ability to metastasize to the distal organs.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The similar findings were also found in other eIF3 subunits [8,11,18,19]. Clonality and migration are the basis for cancer cells' ability to metastasize to the distal organs.…”
Section: Discussionsupporting
confidence: 79%
“…Overexpression of eIF3a promotes malignant transformation [4], while down-regulation of eIF3a reverses the malignant phenotypes of cancer cells [12], including breast [13], cervical [14], esophageal [15], lung [16] and gastric cancers [17]. It is reported that silencing eIF3b results in inhibited proliferation and stimulated apoptosis in colon cancer and glioblastoma cells [18,19]. EIF3c displays its oncogenic roles possibly through promoting protein synthesis by hyperactivating the translation machinery or inhibiting the tumor suppressor merlin [4,20], and is found elevated in testicular seminomas [21] and meningiomas [20].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of eIFs is common in numerous types of cancer and the aberrant expression of several eIFs, including eIF3b (22), eIF4e (23) and eIF5a (24), has also been observed in tissues obtained from patients with glioma, emphasizing the critical role of eIFs in glioma. The upregulation of eIF3c, a component of the eIF3 complex, has been reported in several tumour types, including colon cancer (14), testicular seminoma (12) and meningioma (25).…”
Section: Discussionmentioning
confidence: 99%
“…Although eIF3b is highly expressed in several forms of cancer (52)(53)(54)(55) and its down-regulation has been shown to inhibit the proliferation and metastatic potential of colon, bladder, and prostate cancers (52,53), little is known about eIF3b function(s) at the molecular level. Previous research indicated that eIF3b serves as a binding scaffold for the other core subunits and for eIF2 (47, 49 -51), whereas its interaction with eIF3a, eIF3j, and eIF1a ensures proper formation of the scanning-arrested conformation required for stringent AUG recognition (56).…”
Section: Discussionmentioning
confidence: 99%